(untitled) (Studia Prawnicze / The Legal Studies, 1964)
Supervision in administration is not a new concept, but this term can mean different things. Depending on the organizational system, its meaning and forms may change. The supervision in a system of democratic centralism is particularly important. The emergence of a new category of bodies, which undoubtedly are the bodies of the workers’ self-management, also creates a new supervision problem. First of all, there is a division into the state supervision and the public supervision, depending on the subject exercising supervision and the objective of this supervision. The state supervision exercised by state bodies concerns the functioning of the workers’ self-management and is justified by the fact that the bodies of the workers’ self-management are entrusted with the performance of certain tasks of the state administration. This supervision is built on the principles of multi-levelness; first of all, it is carried out by the enterprise director. It comes down to control over the decisions of the self-management bodies and the ability to suspend their implementation in case of non-compliance with the provisions of the law or a mandatory plan. The director is responsible to the Minister for this supervision. In addition, the director may propose the dissolution of the workers’ council in case of mismanagement of the enterprise. Public supervision is exercised by the respective bodies of the trade unions. The term “public” does not mean that we are dealing with fundamentally different tools of supervision. The difference is determined only by the nature of the supervisory bodies and the objectives of supervision. The very core of this supervision is in the unity of the workers’ self-management with the trade unions, and it is directed to the organizational tasks of the workers’ self-management. An important tool of the supervision is the right to dissolve the workers’ council by the main board of the relevant trade union in the event that the plant staff can express no-confidence in the workers’ council, or if violations are found in the council’s activities that are detrimental to the interests of the staff or the enterprise. An act of supervision should also be considered as an approval of regulations for bodies of the workers’ self-management: the conference of workers’ self-management and the workers’ council. The self-management is indirectly supervised by the staff of the state enterprise itself through its right to demand the dissolution of the workers’ council and issue resolutions on the recall of the council members. Supervision also takes place within the organization of the workers’ self-management itself, however, it is limited to only one event — the approval of the election of the chairman and secretary of the workers’ council by the conference of the workers’ self-management, and in case of the election of the workers’ council presidium, it is limited to the approval of this presidium. Considering workers’ self-management as a unique form of carrying out the tasks of state administration, we should also take into account the forms of general supervision over the state administration along with the forms of supervision peculiar only to the workers’ self-management. Here we have in mind the supervision under the code of administrative jurisdiction exercised over the acts of the bodies of the workers’ self-management, and these acts can be considered administrative decisions within the meaning of this code. For example, it may concern decisions regarding the award of prizes from the factory fund. The activities of the workers’ self-management must also be under the general supervision of the public prosecutor to the same extent and on the same grounds as the activities of any administrative body. In future, we can also expect the specific supervision by local authorities (people’s councils) taking into account the general social and political basis of bodies of the people’s councils and workers’ self-management. The current laws provide for the sole right of the people’s councils to come up with a proposal to dissolve the workers’ council in case of mismanagement of the enterprise.